Kemampuan pemahaman konsep matematis peserta didik kelas v pada materi akar pangkat tiga - Hasanudin Hasanudin; Iyam Maryati (Institut Pendidikan Indonesia, 2023)
Understanding the concept is a very important aspect in learning, because students understand the concept so they can develop their abilities in each subject. The aim of the research is to analyze students' ability to understand mathematical concepts. The method applied in this study was descriptive method. The research subjects were fifth grade students. The instrument used in this research was a test of students' mathematical concept understanding ability, which totaled 4 questions according to indicators of students' understanding of mathematical concepts. After data collection, the researcher analyzed the results of working on the ability to understand mathematical concepts and the results of the interviews to see the ability to understand students' mathematical concepts. Based on data analysis, it can be concluded that the ability to understand mathematical concepts in class V students at SDIT PERSIS Tarogong is still low, as evidenced by the presence of errors in solving mathematical comprehension ability questions, especially on indicators of using, utilizing, choosing certain procedures or operations and applying concepts or problem-solving algorithms in cube root material.Pemahaman konsep merupakan suatu aspek yang sangat penting dalam pembelajaran, karena siswa memahami konsep maka mereka dapat mengembangkan kemampuannya dalam setiap mata pelajaran. Tujuan penelitian adalah menganalisis kemampuan pemahaman konsep matematis siswa. Metode yang diterapkan dalam penelitian ini yaitu metode deskriptif Subjek penelitiannya adalah siswa kelas V. Instrumen yang digunakan dalam penelitian ini adalah tes kemampuan pemahaman konsep matematis siswa yang berjumlah 4 soal sesuai dengan indikator pemahaman konsep matematis siswa. Setelah pengumpulan data, peneliti menganalisis hasil pengerjaan soal kemampuan pemahaman konsep matematis dan hasil wawancara untuk melihat kemampuan pemahaman konsep matematis siswa. Berdasarkan analisis data dapat disimpulkan bahwa kemampuan pemahaman konsep matematis siswa kelas V SDIT PERSIS Tarogong masih rendah yang dibuktikan dengan terdapatnya masih ada kesalahan menyelesaikan soal kemampuan pemahaman matematis terutama pada indikator menggunakan, memanfaatkan, memilih prosedur atau operasi tertentu dan mengaplikasikan konsep atau algoritma pemecahan masalah dalam materi akar pangkat tiga.